A framework for evaluating the mobile augmented reality systems for ubiquitous and interactive cultural learning. (2017) - Chiang, Cheng-Wei; Cheng, Li-Chieh; Liu, Jing-Wei; Lin, Chien-Ku
Mobile augmented reality (MAR) is an increasingly popular technology for enhancing how students interact with and learn about the cultural environment and cultural objects in the physical world. In order to ensure successful launch the mobile augment reality of cultural interactive learning tool, it is extremely important to predict the delighted value of design alternatives systematically based on the common language understood by both students and designers. However, the framework for communicating and evaluating such value from interested perspective is not available in the literature. Therefore, the objective of this research is to extract key frameworks of delighted value from interested perspective and develop an effective algorithm to evaluate MAR cultural learning system. These frameworks, name as CARE framework in brief, included communication, association, reflection, and engagement. The perception differences of MAR cultural learning paper prototypes were conducted to verify the validity of CARE framework for comparative studied. The findings of this study demonstrated that CARE framework was effective for solution designing in MAR cultural interactive learning tool.